Co‐evolution of cleaning and feeding morphology in western Atlantic and eastern Pacific gobies. (6th January 2020) - Huie, Jonathan M.; Thacker, Christine E.; Tornabene, Luke
Abstract: Cleaning symbioses are mutualistic relationships where cleaners remove and consume ectoparasites from their clients. Cleaning behavior is rare in fishes and is a highly specialized feeding strategy only observed in around 200 species. Cleaner fishes vary in their degree of specialization, ranging from species that clean as juveniles or facultatively as adults, to nearly obligate or dedicated cleaners. Here, we investigate whether these different levels of trophic specialization correspond with similar changes in feeding morphology. Specifically, we model the evolution of cleaning behavior across the family Gobiidae, which contains the most speciose radiation of dedicated and facultative cleaner fishes. We compared the cranial morphology and dentition of cleaners and non‐cleaners across the phylogeny of cleaning gobies and found that facultative cleaners independently evolved four times and have converged on an intermediate morphology relative to that of dedicated cleaners and non‐cleaning generalists. This is consistent with their more flexible feeding habits. Cleaner gobies also possess a distinct tooth morphology, which suggests they are adapted for scraping parasites off their clients and show little similarity to other cleaner clades. We propose that evolutionary history and pre‐adaptation underlie the morphological and ecological diversification of cleaner fishes.